TI_GERICHTE 52.2016.555 vom 8. August 2017 , Approvazione dei conti consuntivi di un Comune e di un'Azienda acqua potabile - TI Tribunale d'appello (2017)
Approvazione dei conti consuntivi di un Comune e di un'Azienda acqua potabile